CYP2D6 and IL-6 C-174G variants in schistosomiasis haematobia - Cardoso, R. (2016)
Aim: Study polymorphic variants in CYP2D6 and the C-174G promoter polymorphism of the IL-6 gene on S. haematobium infected patients from and endemic area of Guinea Bissau. Background: - Schistosome egg associated catechol estrogens induce tumor-like phenotypes in urothelial cells and might cause schistosomiasis associated infertility (Botelho et al, Trends in Parasitol, 2015); - The cytochrome P450 (CYP) genes are involved in estrogen biosynthesis and metabolism and generation of DNA damaging procarcinogens (Blackburn et al, Cancer Causes and Control, 2015); - Very high or very low levels of IL-6 are associated with estrogen metabolism imbalance.